The Ibtiyar in the Poetry of ʿUmar Ibn AbīRabīʿah: Its Causes and Manifestations - AL-Mutairi, Hind Abdulrazaq (Arts for Linguistic & Literary Studies, 2021)
The current study in its title "The Ibtiyar in the Poetry of ʿUmar Ibn AbīRabīʿah: Its Causes and Manifestations" deals with a prominent feature of the poetry of ʿUmar Ibn AbīRabīʿah, the pioneer of sensory Ghazal in classical Arabic literature. However, this feature has not been studied carefully, despite the old reference of it in some classical narrative books. This feature was called by Abū al-Faraj al-IṣbahānīIbtiyar in describing, particularly the Poetry of ʿUmar Ibn AbīRabīʿah, and he defined this term as "when a person does something, mentions it, and be proud of it". This study seeks to discuss this distinctive feature of the poet’s poetry since those who have studied Umar’s poetry did not notice it. It will trace its causes and motivations from the life of the poet himself and from the anecdotes that were narrated about him on the one hand, and from the traditions of the Arab culture on the other hand. Then, the study will try to clarify the manifestations of this poetic feature through analyzing samples of ʿUmar Ibn AbīRabīʿa's poetry, concluding that this feature of Ibtiyar was psychological, rather than a realistic one.